Kontemplasi atau Konservasi? Makna dan Motif “Merenungkan Taurat TUHAN” dalam Mazmur 1:2b melalui Penyelidikan Naskah dan Sejarah - Prabowo, Paulus Dimas; Lelono, Joko; Modok, Agustina Sulastri; Titus, Titus (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
The word ‘meditate’ in Psalm 1:2b has various translations in ancient manuscripts, which are at least divided into two camps, namely manuscripts that support the translation ‘meditate’ including the Masoretic, Septuagint, Theodotion, Peshitta, Vulgate, and Targum and manuscripts that support the translation ‘speak aloud’ including Aquila, Symmachus, Quinta, Sexta, and Syro-Hexapla. The translation of ‘meditate’ relates to reading quietly and paying attention to the mind, while the translation of ‘speak aloud’ relates to reading out loud for others to hear. In turn, it appears that there are differences in motives between the two, namely the motives of contemplation and conservation. Based on a study using the textual criticism method, with consideration of consistency and context, it can be seen that the blessed according to Psalm 1:2b are those who like to contemplate the Law of the LORD. The contemplation activity is private, in the context of learning, with the practice of reading silently. The goal is to experience spiritual growth and knowledge.